High-value products from microalgae—their development and commercialisation - Borowitzka, Michael A (Journal of applied phycology, 2013)
Microalgae (including the cyanobacteria) are established commercial sources of high-value chemicals such as β-carotene, astaxanthin, docosahexaenoic acid, eicosahexaenoic acid, phycobilin pigments and algal extracts for use in cosmetics. Microalgae are also increasingly playing a role in cosmaceuticals, nutraceuticals and functional foods. In the last few years, there has been renewed interest in microalgae as commercial sources of these and other high-value compounds, driven in part by the attempts to develop commercially viable biofuels from microalgae. This paper briefly reviews the main existing and potential high-value products which can be derived from microalgae and considers their commercial development with a particular focus on the various aspects which need to be considered on the path to commercialisation, using the experience gained in the commercialisation of existing algae products. These considerations include the existing and potential market size and market characteristics of the product, competition by chemically synthesised products or by ‘natural’ compounds from other organisms such as fungi, bacteria, higher plants, etc., product quality requirements and assurance, and the legal and regulatory environment.